Exploring the mediating role of serum vitamin D in the link between dietary live microbes intake and obesity: a cross-sectional real-world study - Liu, Chan; Zheng, Huiling; Xu, Wenming; Zhu, Xiaoxiao; Li, Mei; Liu, Lijuan (Frontiers in Nutrition, 2025)
BackgroundExisting research results suggest a correlation between body mass index (BMI) and serum vitamin D levels, as well as the intake of live microbes from dietary sources. However, it is essential to further investigate whether serum vitamin D could serve as a mediator in the relationship between the consumption of dietary live microbes and obesity, as this connection remains to be elucidated.MethodsWe analyzed data from 18,099 participants in the 2007–2018 National Health and Nutrition Examination Survey (NHANES), focusing on obesity [assessed via BMI and waist circumference (WC)], serum vitamin D levels, and the dietary intake of live microbes (evaluated both as a continuous variable and a three-level categorical variable). A composite category “MedHi” was used to reflect the intake of foods containing medium (104–107 colony-forming units (CFU/g)) or high (>107 CFU/g) levels of live microbes. Mediation analysis was conducted to explore how serum vitamin D potentially mediates the relationship between the dietary intake of live microbes and obesity.ResultsAfter adjusting for potential confounding factors, it was found that both vitamin D and the MedHi consumption were strongly and negatively associated with obesity. Mediation analysis revealed that serum vitamin D mediated the relationship between the dietary intake of live microbes and BMI, WC, obesity, and abdominal obesity with mediated proportions of 14.6, 12.5, 13.0, and 12.5%, respectively.ConclusionThe positive association between the dietary intake of live microbes and obesity risk is partly mediated by serum vitamin D. Foods with higher microbial concentrations could be beneficial.